Changes in Global Tropospheric OH Expected as a Result of Climate Change Over the Last Several Decades. Issue 18 (26th September 2018) - Nicely, Julie M.; Canty, Timothy P.; Manyin, Michael; Oman, Luke D.; Salawitch, Ross J.; Steenrod, Stephen D.; Strahan, Susan E.; Strode, Sarah A.
Abstract: The oxidizing capacity of the troposphere is controlled primarily by the abundance of hydroxyl radical (OH). The global mean concentration of tropospheric OH, [OH] TROP (the burden of OH in the global troposphere appropriate for calculating the lifetime of methane) inferred from measurements of methyl chloroform has remained relatively constant during the past several decades despite rising levels of methane that should have led to a decline. Here we examine other factors that may have affected [OH] TROP such as the changing values of stratospheric ozone, rising tropospheric H2 O, varying burden of NO x (=NO+NO2 ), rising temperatures, and widening of the climatological tropics due to expansion of the Hadley cell. Our analysis suggests the positive trends in [OH] TROP due to H2 O, NO x, and overhead O3, and tropical expansion are large enough (Δ [OH] TROP  = +0.95 ± 0.18%/decade) to counter almost all of the expected decrease in [OH] TROP due to rising methane (Δ [OH] TROP  = −1.01 ± 0.05%/decade) over the period 1980 to 2015, while variations in temperature contribute almost no trend (Δ [OH] TROP  = −0.02 ± 0.02%/decade) in [OH] TROP . The approximated impact of Hadley cell expansion on [OH] TROP is also a small but not insignificant factor partially responsible for the steadiness of tropospheric oxidizing capacity over the past several decades, which free‐running models likely do not capture. Key Points: Trends in OH between 1980 and 2015 were modeled using observed ozone column, water vapor, methane, model‐simulated NO x, and Hadley cell width Most (94%) of the expected, CH4 ‐induced decline in OH was offset by increases due to H2 O, NO x, overhead O3, and tropical widening (in order of impact) Trends depend on time frame examined; NO x and overhead O3 drive most of OH increase between 1980 and 2005